ICRISAT Sahelian Center (ISC) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
ICRISAT Sahelian Center (ISC)The Sahelian Centre, in Niamey, Niger, is ICRISAT's principal research base for the Sahelian region of West Africa. The primary areas of focus at ISC are the improvement of pearl millet, the area's principal crop, and...